Ladderlike carbon nanoarrays on 3D conducting skeletons enable uniform lithium nucleation for stable lithium metal anodes. Issue 42 (8th May 2018) - Liu, Lin; Yin, Ya-Xia; Li, Jin-Yi; Guo, Yu-Guo; Wan, Li-Jun
Abstract : Well-arranged ladderlike carbon nanoarrays can bring about homogenous Li-ion flux and reduced local current density, thus regulating uniform Li nucleation/growth. Abstract : Inhomogeneous Li nucleation leads to uncontrolled dendritic Li growth, seriously impeding the practical applications of Li metal-based batteries. Herein, we demonstrate that a well-arranged ladderlike carbon nanoarray membrane on 3D conducting skeletons can bring about homogenous Li-ion flux and reduced local current density, thus regulating uniform Li nucleation and dendrite-free Li growth. The favorable Li deposition behavior contributes to a high Coulombic efficiency (99%) and an ultralong cycling life (1000 h) with a low overpotential.